Performance of used jars and closures for canned pickling solutions and syrup - Joven, Nieves G.; Kabigting, Amelia L. (1969.)
Three kinds of jars - new jars with new closures, used jars with used closures, and used jars with new closures were used for packing and preserving of sweet-sour solution and 50°Brix syrup. Different physical tests: vacuum and headspace; chemical tests: % soluble solids, pH and % titrable acidity and microbiological tests: total plate count and yeast and mold count were used to assess the performance of these jars before and after one week of storage at room temperature. There was no trend in the results of the tests using closures with rubber gaskets so no conclusive recommendations can be given. There was significant difference at 5% level in vacuum due to storage time in the case of 50°Brix solution packed in used jars and closures lined with polyvinyl chloride. Other tests did not show any significant difference. Within the limits of this experiment, used jars with used closures lined with polyvinyl chloride can be used for preserving sweet-sour solution; but they cannot be used for 50°Brix syrup.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Glass fruit jars; Canning and preserving -- Equipment and supplies